Wittgenstein on the Grounds of Religious Faith: A Kantian Proposal - Hanne Appelqvist (Wiley Blackwell, 2022)
This paper argues that there is an important continuity between Wittgenstein’s early remarks on religion and his later treatment of the theme as it appears in his lectures in the 1930s and in his personal diary notes at that time. This continuity pertains to three features. First, the early and later Wittgenstein share a critical stance on methodological naturalism, that is, the view that the method of philosophy is relevantly similar to that of the natural science. Importantly, religion figures as one of Wittgenstein’s examples of the limits of the factual language of natural sciences. Second, both the early and the later Wittgenstein connect religion to the problem of seeing one’s life as meaningful while denying the possibility of establishing any objectively understood meaning of life. Third, both evoke the idea of different types of judgments, the conditions of which are independent of each other. Although religious faith is not grounded in factual knowledge and cannot be justified by appeal to empirical evidence or conceptual argumentation, it is not groundless either. Rather, in accordance with Kant who claims that faith may have a nontheoretical justification, Wittgenstein shows that religious faith may result from a personal experience of one’s life as a meaningful whole.